Investigating the Quality of Life in Patients with Tuberculosis: A Study in Southwest Iran - Moradi, Shiva; Asadiyan, Negin; Piri, Kosar; Ahvazi, Maryam Roze; Mojdehi, Parastoo Daemi; Sharifpour, Mojtaba; Damsaz Hafshejani, Nazanin; Rajabi Pour, Saba; Rahime, Malihe; Shamshiry, Raziyeh; Darabiyan, Pouriya; Salehi, Shaghayegh; et al. (International Journal of Ayurvedic Medicine, 2024)
Introduction: Tuberculosis is one of the most common diseases of the present era, which affects the quality of life of patients. The present study was conducted with the aim of investigating the quality of life of patients with pulmonary tuberculosis referred to health centers in Ahvaz city. Methods: The current research is a cross-sectional study that was conducted on 75 patients with tuberculosis who referred to the health centers of Ahvaz city in 2021 through a simple random sampling method of patients with tuberculosis. Data collection tools include: demographic variables checklist and sf-36 standard questionnaire (Survey short-form 36-item health) which was collected in person. After completing the sampling, the data were analyzed using SPSS version 21 statistical software and descriptive and inferential statistical tests using independent t-tests, analysis of variance and chi-square. Results: The lowest average score was related to limited physical activity followed by psychological problems and social functioning. Also, independent t-test results showed that the average scores of quality of life in men and women, pulmonary and non-pulmonary tuberculosis patients, and the patient's place of residence are statistically and significantly different. Conclusion: According to the results, tuberculosis and its treatment affect the social performance, psychological and emotional aspects of the patients' quality of life.